2023
DOI: 10.1101/2023.09.27.559693
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Timing specific parental effects of ocean warming in a coral reef fish

L.C. Bonzi,
R.K. Spinks,
J.M. Donelson
et al.

Abstract: Population and species persistence in a rapidly warming world will be determined by an organisms’ ability to acclimate to warmer conditions, especially across generations. There is potential for transgenerational acclimation, but the importance of ontogenetic timing in the transmission of environmentally induced parental effects remains mostly unknown. We aimed to disentangle the contributions of two critical ontogenetic stages (juvenile development and adult reproduction) to transgenerational plasticity, by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Samples were processed as already in Bonzi et al (2023). Briefly, total RNA was isolated from homogenized whole livers using a mir Vana miRNA Isolation kit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were processed as already in Bonzi et al (2023). Briefly, total RNA was isolated from homogenized whole livers using a mir Vana miRNA Isolation kit.…”
Section: Methodsmentioning
confidence: 99%
“…If adaptive, non-genetic inheritance through environmentally induced parental effects might enable acclimation to persistent environmental changes, such as global warming (Donelan et al, 2020; Donelson, Salinas, Munday, & Shama, 2018). In a coral reef fish, the spiny chromis Acanthochromis polyacanthus (Bleeker 1855), for instance, studies have shown that parental developmental exposure to elevated temperature can provide transgenerational acclimation to ocean warming and restoration of aerobic scope in offspring through molecular changes in lipid and carbohydrate metabolism, as well as immune system and transcriptional regulation (Bernal, Ravasi, Rodgers, Munday, & Donelson, 2021; Bernal, Schmidt, Donelson, Munday, & Ravasi, 2022; Bonzi et al, 2023; Donelson, Munday, McCormick, & Pitcher, 2012; Ryu, Veilleux, Donelson, Munday, & Ravasi, 2018; Veilleux et al, 2015). The relative importance of fathers and mothers in such acclimation process, however, is unknown, but has implications on adaptive potential.…”
Section: Introductionmentioning
confidence: 99%
“…RNA-seq data can be found under the BioProject PRJNA998209. Electronic supplementary material is available online [89]. Declaration of AI use.…”
mentioning
confidence: 99%